2007
DOI: 10.1007/s00705-007-0940-2
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection with different subtypes of feline immunodeficiency virus can complicate subtype assignment by phylogenetic analysis

Abstract: Phylogenetic analyses of the V3-V5 region of the env gene are used to determine Feline immunodeficiency virus (FIV) subtypes but can be complicated by co-infection with different subtypes or the presence of recombinant subtypes. FIV in blood samples from 30 domestic cats in New Zealand was subtyped by sequencing three overlapping fragments of the V3-V5 region of the env gene and 467 bp of the gag gene. Phylogenetic analyses revealed that the isolates clustered with subtype A and C viruses. Seven samples showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Fca , Retroviruses have been documented to have relatively rapid rates of recombination due to the presence of a diploid genome (that is, two identical copies of ssRNA) and the occurrence of multiple infection (Hu and Temin, 1990). Naturally-occurring multiple FIV Fca , infection, either as a result of co-infection or superinfection, has been identified in cats from Australia, USA and NZ (Kyaw-Tanner and Robinson, 1996;Bachmann et al, 1997;Kann et al, 2007;Hayward and Rodrigo, 2008). Several of these cases involve two strains of the same subtype (Kyaw-Tanner and Robinson, 1996;Hayward and Rodrigo, 2008).…”
Section: Recombination In Fivmentioning
confidence: 99%
“…Fca , Retroviruses have been documented to have relatively rapid rates of recombination due to the presence of a diploid genome (that is, two identical copies of ssRNA) and the occurrence of multiple infection (Hu and Temin, 1990). Naturally-occurring multiple FIV Fca , infection, either as a result of co-infection or superinfection, has been identified in cats from Australia, USA and NZ (Kyaw-Tanner and Robinson, 1996;Bachmann et al, 1997;Kann et al, 2007;Hayward and Rodrigo, 2008). Several of these cases involve two strains of the same subtype (Kyaw-Tanner and Robinson, 1996;Hayward and Rodrigo, 2008).…”
Section: Recombination In Fivmentioning
confidence: 99%
“…Neither the prevalence of FIV infection in Brazil nor all prevailing subtypes are known. Identification of circulating subtypes from different areas of Brazil is essential to develop strategies for molecular diagnosis, since the genetic diversity is high [18]. A recent publication declared that Brazilian FIV strains and their epidemic spread have not been deeply characterized [22].…”
Section: Element (Ccctttgaggaagatgtgtcatatgaatccatt) Incorporating Mluimentioning
confidence: 99%
“…Like other lentiviruses, FIV exhibits extensive genetic variation [18,32]. The pol and gag genes encode viral enzymes and core proteins respectively, and are relatively highly conserved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recombination may modify viral properties and aid adaptation to new host species. This applies also to RNA viruses infecting cats and dogs; for example, group 1 feline and canine coronaviruses [8,21], feline calicivirus [4], feline immunodeficiency virus [2,7,10,29], and canine distemper virus [6]. Recently Shackelton et al [31] found some evidence of natural recombination among porcine, mink, and rodent parvoviruses by analyzing the genetic data deposited in databases, and discussed the possibility that recombination may be important in the natural evolution of parvoviruses, especially in circumstances where parvoviruses cause persistent infections.…”
mentioning
confidence: 99%